2011
DOI: 10.1111/j.1365-2745.2010.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Norway spruce diversifies the fire regime in boreal European forests

Abstract: 1. Global wildfire activity and biomass burning have varied substantially during the Holocene in both time and space. At the regional to continental scale, macroclimate is considered to be the predominant control regulating wildfire activity. By contrast, the role of forest tree composition is often considered as a subsidiary factor in studies addressing temporal variation in regional wildfire activity.2. Here, we assemble a spatially comprehensive data set of 75 macroscopic charcoal records that reflect local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 70 publications
3
79
0
Order By: Relevance
“…Fire appears to decrease in sites as P. abies becomes regionally established in Finland (7800-5500 cal years BP) and in Sweden (5500-3000 cal years BP). This negative correlation between P. abies and fire has been well documented for Fennoscandia, with both the spread of P. abies being held responsible for a reduction in fire (Ohlson et al 2011), and a decrease in fire being blamed for the subsequent spread of P. abies (Bjune et al 2009). Here, our compilation indicates that the change in fire regime occurs once P. abies is regionally established.…”
Section: Discussionmentioning
confidence: 99%
“…Fire appears to decrease in sites as P. abies becomes regionally established in Finland (7800-5500 cal years BP) and in Sweden (5500-3000 cal years BP). This negative correlation between P. abies and fire has been well documented for Fennoscandia, with both the spread of P. abies being held responsible for a reduction in fire (Ohlson et al 2011), and a decrease in fire being blamed for the subsequent spread of P. abies (Bjune et al 2009). Here, our compilation indicates that the change in fire regime occurs once P. abies is regionally established.…”
Section: Discussionmentioning
confidence: 99%
“…Yet smaller scale disturbances, caused by heart-rot, insect attacks, wind throws, snow breaks, may result in patch or gap dynamics where single trees (gaps) or small groups of trees (patches) die and the forest develops a more varied age structure (Kuuluvainen & Aakala 2011). The variable role of fire as a disturbance agent is also emphasized by Ohlson et al (2009Ohlson et al ( , 2011 who showed that fires have varied considerably across Fennoscandia, having often been less extensive and frequent than previously considered (e.g., Zackrisson 1977). The frequency and effects of fires depended on both climate (few fires in oceanic climates) and the establishment of spruce as a dominant forest tree (resulting in far fewer fires than before) (although Hellberg et al (2009) found that fire was an important disturbance agent in spruce forests in their study area).…”
Section: Natural Dynamics Of Nordic Forestsmentioning
confidence: 99%
“…Natural fire frequencies in these boreal habitats vary considerably in space and time but are much lower than those of the managed coastal heathlands [22][23][24][25]. To evaluate evolutionary impacts of the anthropogenic fire regimes, we assessed germination responses to smoke of Calluna seeds [9,11,13 -15]).…”
Section: Introductionmentioning
confidence: 99%